Views on retirement, preparations and level of retirement anxiety among selected government employees in Iloilo City - Domingo, Hessel Anne N.
This study aimed to find out the views on retirement, preparations, and level of retirement anxiety among selected government employees in Iloilo City. A total of 50 respondents from 10 different government agencies participated in the study. The ages of the respondents ranged from 45 to 66. Their number of years in service is within 15 to 50. A Likert Scale was administered to find out the views on retirement of the respondents. Meanwhile, a survey questionnaire which consisted of two parts (the financial and personal and psychological preparation) was made to find out the preparations of retirables with regards to retirement. To measure the retirement anxiety, the researchers utilized a modified Retirement Anxiety scale based on a Generalized Anxiety Scale., Results showed that the respondents were not looking forward on retirement. Most of them held negative views about it. Most of the respondents were not too confident that they have enough savings for retirement. when they do retire, they planned to engage most of their time with their families and participate in religious and community activities. with regards to the retirement anxiety of the selected government employees, they were generally low. They do not worry too much about financial, emotional and psychological concerns of a person who is retiring.